"My Body Hates Me": A Qualitative Analysis of the Experience of Functional Nausea in Adolescent Girls and Their Mothers - Michelle A. T. Cole; Dima Qu'd; Marcus G. Wild; Alexandra C. Russell; Aimee R. Caillet; Amanda L. Stone (MDPI AG, 2020)
Nausea is a somatic sensation typically associated with the need to vomit in order to remove a toxin from the body. When nausea occurs in the absence of a specific structural cause or toxin, it is classified as a functional gastrointestinal disorder (FGID). Functional nausea was newly recognized in 2016 as a FGID in children and little is known about its prevalence, course or patient experiences. Nausea co-occurring with functional abdominal pain in childhood has been associated with long-term risk for anxiety and ongoing somatic symptoms into young adulthood. However, few studies have focused uniquely on the experience and impact of nausea on youth. The present study aimed to qualitatively understand the experiences of adolescent girls with functional nausea and their parents. Five mother-daughter dyads were recruited from a specialized pediatric gastroenterology clinic focused on nausea and completed semi-structured interviews. Interviews were transcribed and coded using interpretive phenomenological analysis (IPA). Four main themes emerged: nausea interference, body frustration, misunderstanding of symptoms, and maternal helplessness and guilt. These themes were similar to prior studies on the experiences of youth with chronic pain but also indicated unique challenges due to nausea, such as significant food restriction and subsequent weight loss.